2022
DOI: 10.4103/jcd.jcd_469_21
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal microcracks induced by endodontic procedures: A scientometric and bibliometric analysis

Abstract: Background: Due to the large number of publications relating the occurrence of dental microcracks to endodontic procedures, this bibliometric study evaluated the scientific pattern and trends in literature and provided an overview of scientific production in this context. Aim: To analyze, quantify, and characterize the scientific production and trends of published articles evaluating dentinal microcracks formation after endodontic treatment procedures between 2010 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Bibliometric analysis is a popular method that exhibits the tendency of different subfields. [29][30][31]33,34 Besides, the deficiencies in the endodontic literature may be mapped. 30,31 This study emphasis on the evolution of hotspots, publication trends, citation structures, prolific authors, institutional affiliations, and countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bibliometric analysis is a popular method that exhibits the tendency of different subfields. [29][30][31]33,34 Besides, the deficiencies in the endodontic literature may be mapped. 30,31 This study emphasis on the evolution of hotspots, publication trends, citation structures, prolific authors, institutional affiliations, and countries.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31]33,34 Besides, the deficiencies in the endodontic literature may be mapped. 30,31 This study emphasis on the evolution of hotspots, publication trends, citation structures, prolific authors, institutional affiliations, and countries. By analyzing publication volume and citation metrics, researchers may better understand the impact and importance of biochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, these analyses have only described trends. 19,20 Indeed, some analyses have indicated that there were trends 21 ; that there was no clear trend 22 ; that the increase in the number of publications was linear, 23 polynomial, 24 or exponential 25 ; or that its trends followed a discontinuous regression pattern. 26 This information will guide researchers in dentistry when they make decisions about which journal to publish in and therefore to which publisher they should submit their article.…”
Section: Introductionmentioning
confidence: 99%